Kinerja Keuangan PT. Krakatau Steel Tbk Membaik?: Tinjauan Analisis Laporan Keuangan - Abdul Latif; Primaraga Sumantri Indra Wicaksana; Nani Hartati; Nur Hidayati (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2023)
Financial reports are an accurate information instrument for assessing company performance for investors, companies and the public. PT. Krakatau Steel (Persero), Tbk, is the only state-owned company in Indonesia's steel industry. Thus, the company's status and performance are highly monitored by the government, investors, and the general public because it is a benchmark for the development of the steel industry. Issues related to the company's poor financial performance in several periods made the researchers aim to analyze the performance of the company's financial statements. This research aims to analyze the performance of the company's financial ratios items such as profitability, solvency, activity, liquidity, and profit growth ratios for the 2018-2021 period. The analytical method used in this study is a descriptive quantitative analysis of the company's financial ratios. The results of the study assume that the profitability ratio is in the unhealthy criteria, the liquidity ratio is assumed to be in the unhealthy criteria, the activity ratio is assumed to be in the unhealthy criteria, the solvency ratio is assumed to be in the reasonably good criteria, the growth ratio is assumed to be in the unfavourable criteria in the study period.